2015
DOI: 10.1186/s12864-015-1509-1
|View full text |Cite
|
Sign up to set email alerts
|

High throughput profiling of the cotton bollworm Helicoverpa armigera immunotranscriptome during the fungal and bacterial infections

Abstract: BackgroundInnate immunity is essential in defending against invading pathogens in invertebrates. The cotton bollworm, Helicoverpa armigera (Hübner) is one of the most destructive lepidopteran pests, which causes enormous economic losses in agricultural production worldwide. The components of the immune system are largely unknown in this insect. The application of entomopathogens is considered as an alternative to the chemical insecticides for its control. However, few studies have focused on the molecular mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
96
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 81 publications
2
96
0
1
Order By: Relevance
“…The differentially expressed genes (DEGs) were filtered out by R package DEGseq with a cut-off P-value<0.001 (Wang et al, 2010). The genes were considered differentially or significantly expressed if they had a P value<0.05 and a fold change of either>2 or <0.5 (Xiong et al, 2015).…”
Section: Assembly Of Transcriptomes and Functional Classificationmentioning
confidence: 99%
“…The differentially expressed genes (DEGs) were filtered out by R package DEGseq with a cut-off P-value<0.001 (Wang et al, 2010). The genes were considered differentially or significantly expressed if they had a P value<0.05 and a fold change of either>2 or <0.5 (Xiong et al, 2015).…”
Section: Assembly Of Transcriptomes and Functional Classificationmentioning
confidence: 99%
“…There is a conserved glycine (Gly) behind the Cys‐4 of IML‐B and the residues at the first site after Cys‐4 of IML‐A are Val/Ile/Leu/Ala. This feature is not only seen in T. xiaojinensis IMLs but also in other identified IMLs (Rao et al ., , b; Xiong et al ., ). It is known that the four to six Cys residues in CTLDs are responsible for formation of disulfide bonds, and thus motif signatures around Cys, conserved in most IMLs, may have important effects on protein sorting.…”
Section: Discussionmentioning
confidence: 97%
“…The rapid response of cecropin and defensin suggested that because houseflies were infected with C. albicans, they may preferentially respond to the Toll pathway. Other studies have shown that the Toll and IMD pathways can be cooperative and may contribute to the activation of each other (Lemaitre and Hoffmann 2007;Tanji et al 2007, Xiong et al 2015. Defensin and cecropin are predominantly regulated by the Toll pathway, and attacin and diptericin are predominantly regulated by the IMD pathway during the C. albicans infection.…”
Section: Discussionmentioning
confidence: 99%